Resiliensi Mahasiswi Pasca Sarjana yang Mengalami Cerai Hidup - Agung Satria Wijaya; Tomi Sukardi; Akmil Rahmi (Institut Agama Islam Sumatera Barat, 2021)
Married couples are certainly not free from problems and fights. The problems experienced can be triggered by differences in opinion, economic problems, incompatibility issues, and other problems. Some couples are able to solve these problems and often choose a divorce to end their household. The divorce that occurs will have an impact on those who experience it, especially the woman / wife. The impact that is felt can be in the form of physical and psychological. Individuals who experience divorce should have the ability to resilience themselves. Resilience is the ability that a person has to rise from a downturn that occurs due to certain problems. Based on preliminary observations in the field, researchers found that research subjects did not experience the negative effects of divorce. The focus of his research is: 1) the description of post-divorce women's resilience, 2) factors of post-divorce women's resilience, and 3) the impact of post-divorce women's resilience. This study uses qualitative methods with interview and documentation techniques on a key informant, namely a woman who is experiencing a divorce. The results obtained are: 1) the key informant can live his life as a single parent, 2) the resilience factor is motivation and support from the family, 3) the key informant can continue studying in the postgraduate program to live an effective daily life.